(untitled) (International Journal of Environmental Sciences, 2025)
Mangoes are one of the most popular products in Cebu City. They are used in food, cosmetics, and occasionally in the furniture-making industry, which increases their demand each year. This study aims to find an alternative solution to its rising waste problems by turning its seed part into another product to treat Zinc, one of the prevailing minerals in sanitary leachate, because of its electronic waste composition. These mango seed wastes were processed into activated carbon through physical activation, placing it in the furnace at a temperature of 800°C with a controlled oxygen environment. They were tested for adsorption by placing the produced synthetic activated carbon on top of the filter paper in the funnel. Then, a liquid containing the synthetic Zinc with a concentration of 0.13 ppm was poured into the funnel. It showed that after 24 hours in the rotary shaker, the zinc concentration was significantly reduced to an average of 92.83%, revealing that the mango seed is an outstanding material for activated carbon. Mango seed wastes from industries have great potential as a source of activated carbon that influences the treatment of sanitary leachates with a higher concentration of Zinc.